PENGARUH PENGGUNAAN ANTIKOAGULAN TERHADAP MORTALITAS PASIEN COVID-19 DENGAN RISIKO KOAGULOPATI: Systematic Review - Sapphira Mazaya Salsabila (2022)
Background: One of the most common cause of death in hospitalized COVID-19 patients is related with the progression of coagulopathy that caused by hyperinflammatory events thus causing a systemic cytokine storm resulting systemic inflammatory response syndrome (SIRS). In COVID-19 guideline of treatment by Indonesian Association of Pulmonary, Cardiovascular, and Internal Medicine Physicians recommends the use of anticoagulants in all hospitalized COVID-19 patient adjusted with appropriate clinical judgement. This systematic review was conducted to analyze the effect of anticoagulants use on mortality in COVID-19 patients who at risk of coagulopathy. Methods: A systematic review conducted by starting a literature search from May to July 2021. The literature that being analyzed was from Google Scholar, PubMed, EBSCO, and Science Direct database using PRISMA-P 2020. Results: Datas were obtained from nine journals. Eight of them stated that the use of prophylactic and therapeutic doses, has an effect on reducing the mortality rate of COVID-19 patients and one journal did not see a significant difference on mortality of COVID-19 patients. Types of anticoagulant that are widely used in nine journals are heparin and fondaparinux with doses adjusted to coagulation marker. Conclusion:The use of anticoagulant is beneficial in reducing mortality rates in hospitalized COVID-19 patients.